BIOLOGICAL MARKERS IMPORTANCE IN THE DIAGNOSIS OF OSTEOPOROSIS - Loredana Liliana Hurjui; Ion Hurjui; Carmen Delianu; Cristina Claudia Tărniceriu; Alexandra Maria Mârțu; Carina Balcoș; Raluca Jipu; Adina Oana Armencia; Ion Andrei Hurjui; Ruxandra Maria Hârțan; Irina Grădinaru (Romanian Society of Oral Rehabilitation, 2020)
Bone seen as tissue is an extremely dynamic biological system, comprising a series of tightly regulated and synergistic anabolic and catabolic processes that lead to a metabolic homeostasis corresponding to skeletal structures. Osteoporosis is defined as an evolutive disease of the skeletal system characterized by loss of bone mass and alterations in the microarchitecture of bone tissue, resulting in increased bone fragility and the risk of fractures. Osteoporosis has gained a huge resonance in recent years both personally and economically. In this review we are going to present some of the best known bone markers of resorption and bone formation, determined from blood and / or urine samples. Research for new biomarkers, which can predict abnormal bone mass loss at various stages of the disease, is ongoing. The impact of osteoporosis on the susceptibility of the host to periodontal damage is still being understood. It is clear that the efforts should be directed towards the prevention of periodontal disease in patients at risk for osteoporosis. Patients with osteoporosis should benefit from frequent periodontal treatments, especially if periodontal disease is already present. Starting from the studies collected from the literature, it is very interesting to define the relationship of periodontal disease and osteoporosis following a series of markers of bone resorption in patients diagnosed with periodontal disease. A better understanding of the relationship between the two diseases, osteoporosis and periodontal disease, would help in the preventive and therapeutic measures as soon as it is possible.